1995
DOI: 10.1177/001979399504800402
|View full text |Cite
|
Sign up to set email alerts
|

National Union Effectiveness in Organizing: Measures and Influences

Abstract: The percentage of the U.S. work force that is unionized is at its lowest level in more than 50 years. Although many studies have sought the reasons for this decline, few have investigated characteristics of unions themselves as possible factors. This paper focuses on unions as organizations, and applies a model of national union effectiveness to union organizing. The authors propose a composite measure of organizing effectiveness that goes beyond union success in representation elections. An analysis of data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 15 publications
5
26
0
Order By: Relevance
“…Thus, the external threat's emergence was more a factor than was new leadership. National and state affiliates were also critical in developing and implementing plans for transformation, consistent with prior analyses (Fiorito, Jarley, and Delaney 1995;Voss and Sherman 2000).…”
Section: Leadership and Organizationsupporting
confidence: 63%
See 2 more Smart Citations
“…Thus, the external threat's emergence was more a factor than was new leadership. National and state affiliates were also critical in developing and implementing plans for transformation, consistent with prior analyses (Fiorito, Jarley, and Delaney 1995;Voss and Sherman 2000).…”
Section: Leadership and Organizationsupporting
confidence: 63%
“…This point was made previously in broad-based quantitative research on organizing (e.g., Bronfenbrenner 1997;Fiorito, Jarley, and Delaney 1995), and in more extensive and less intensive case studies (e.g., Voss and Sherman 2000). In the present case, the UFF could have pursued other strategies, including abandoning the SUS and focusing on its stronger CC chapters with their higher membership density.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The innovation scale consisted of eleven items (alpha = .77) ranging from associate membership programs to the use of new media and corporate campaigns. It did not include bargaining over organizing (see Fiorito et al 1995:626 for a full list). The innovation scale was a strong, positive determinant of organizing effec-I A few unions initially indicated that they did not have any such agreements, but were later found to have one or more.…”
Section: Other Factorsmentioning
confidence: 99%
“…Later debates have concentrated on the requirements of successful renewal of workplace union organisation either in terms of adoption of strategy (Boxall and Haynes, 1996) or within a discussion of the general context of the future of unions (Fiorito et al, 1995;Hyman, 1996). More recent contributions from Darlington (1994Darlington ( , 2001 and Gall (1998) have filled an important gap by concentrating on the political affiliation of stewards and its influence on workplace organisation.…”
mentioning
confidence: 99%